Proceedings of the 22nd International Database Engineering &Amp; Applications Symposium on - IDEAS 2018 2018
DOI: 10.1145/3216122.3216155
|View full text |Cite
|
Sign up to set email alerts
|

The Deployment of an Enhanced Model-Driven Architecture for Business Process Management

Abstract: Business systems these days need to be agile to address the needs of a changing world. Business modelling requires business process management to be highly adaptable with the ability to support dynamic workflows, inter-application integration (potentially between businesses) and process reconfiguration. Designing systems with the in-built ability to cater for evolution is also becoming critical to their success. To handle change, systems need the capability to adapt as and when necessary to changes in users' r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The relevance about studies about AOM can be confirmed by some recent works found in the literature that used directly or were based on this architectural style, such as for economy mechanics in digital games [3], model-driven architectures [4], [5], data evolution in digital ecosystems [6], meta-modeling architectures [7], and creating dynamic web services [8], [9]. But besides this architectural style is still applied, to the best of our knowledge, except for our previous work with Esfinge AOM Role Mapper [38]- [40], there are no other works in the last five years that focused on advances for the design of AOM architectures.…”
Section: Related Workmentioning
confidence: 75%
See 1 more Smart Citation
“…The relevance about studies about AOM can be confirmed by some recent works found in the literature that used directly or were based on this architectural style, such as for economy mechanics in digital games [3], model-driven architectures [4], [5], data evolution in digital ecosystems [6], meta-modeling architectures [7], and creating dynamic web services [8], [9]. But besides this architectural style is still applied, to the best of our knowledge, except for our previous work with Esfinge AOM Role Mapper [38]- [40], there are no other works in the last five years that focused on advances for the design of AOM architectures.…”
Section: Related Workmentioning
confidence: 75%
“…Several more recent studies employed AOM concepts for several applications and domains, such as for economy mechanics in digital games [3], model-driven architectures [4], [5], data evolution in digital ecosystems [6], meta-modeling architectures [7], and dynamic web services [8], [9]. That can be considered an evidence that this architectural style is still relevant and applied in recent works.…”
Section: Introductionmentioning
confidence: 99%